Analysis and comparison of results of the Mader test in different strokes in agonistic swimmers - Invernizzi, M. G.; Scurati, R.; Pizzini, G. (Biomechanics and Medicine in Swimming X, 2006)
Several studies were performed to analyze both the blood lactate concentration after competitions and to set the optimal intensity level during the training. The aim of this study was to evaluate the differences in lactate production between high level male and female four-strokes-swimmers and the differences in lactate concentrations among these strokes in swimmers of the same gender. Forty male and forty female swimmers performed a modified Mader test in their own discipline. The time for 200m at the threshold speed, the [La-] peak and the [La-]/time at the anaerobic threshold ratio were considered. Male athletes produced more lactate for each stroke than the female counterparts. The higher peak lactate concentration in the male athletes were found in breaststroke, whereas in females athletes the higher peak was found in butterfly.